2018
DOI: 10.1088/1361-6501/aab940
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel new multispectral nanoparticle tracking technique

Abstract: Fast, reliable, and accurate particle size analysis techniques must meet the demands of evolving industrial and academic research in areas of functionalized nanoparticle synthesis, advanced materials development, and other nanoscale enabled technologies. In this study a new multispectral particle tracking analysis (m-PTA) technique enabled by the ViewSizer ™ 3000 (MANTA Instruments, USA) was evaluated using solutions of monomodal and multimodal gold and polystyrene latex nanoparticles, as well as a spark erode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Both instruments also have a capability to estimate nanoparticle concentration based on individual particle counting within the calibrated volume of sample. While the NanoSight uses only one laser source, the ViewSizer deploys three laser sources at different wavelengths, which generally improves both the size and concentration determinations of particles [55].…”
Section: A Residual Particle Populations In the Pure Water And Mastementioning
confidence: 99%
“…Both instruments also have a capability to estimate nanoparticle concentration based on individual particle counting within the calibrated volume of sample. While the NanoSight uses only one laser source, the ViewSizer deploys three laser sources at different wavelengths, which generally improves both the size and concentration determinations of particles [55].…”
Section: A Residual Particle Populations In the Pure Water And Mastementioning
confidence: 99%
“…Offline instruments capable of immersion mode INP measurement include a number of droplet assays, in which sample suspensions are distributed among an array of droplets that are then cooled and frozen (e.g., Budke and Koop, 2015;Harrison et al, 2018;Hill et al, 2014;Whale et al, 2015) as well as other systems in which water is condensed onto particles collected on substrates prior to cooling and freezing (e.g., . As they are designed for analysis of liquid suspensions, droplet freezing assay techniques are commonly used for measurement of INPs suspended in precipitation (e.g., Creamean et al, 2019;Rangel-Alvarado et al, 2015;Michaud et al, 2014;Stopelli et al, 2014;Wright et al, 2014).…”
mentioning
confidence: 99%
“…For NTA, the masking effect of larger particles over smaller ones has been well documented: Tian et al could not achieve simultaneous measurement of 100 and 1000 nm bead mixtures or 100 and 300 nm bead mixtures, and in mixtures of 100 and 200 nm beads, Krueger et al observed a clear bias toward the larger species at all tested ratios . In 2018, McElfresh et al demonstrated that MNTA could address this limitation and accurately measured multimodal mixtures of gold and polystyrene latex particles . One unresolved question was its utility for soft materialsespecially those that undergo size dynamics such as aggregating proteins.…”
mentioning
confidence: 99%